Answer:
18
Step-by-step explanation:
Just divide both sides by - 64
Answer:
x = 10
Step-by-step explanation:
30/35 = (6x-6)/63
210x - 210 = 1890
210x = 2100
x = 10
Answer:
2x+14
Step-by-step explanation:
(3/4)x-7.3+(5/4)x+21.3
(3/4+5/4)x+21.3-7.3
2x+14
0.83Answer:
Step-by-step explanation:
83% means 83 per 100 or 83/100 if you divide 83 by 100 you get 0.83
H = 2f / (m+1)
[multiply by (m+1)]
h(m+1) = 2f
[divide by 2]
f = (h (m + 1)) / 2
3b / (b+2) = 12 / (b+2)
[multiply by (b+2)]
3b = 12
[divide by 3]
b = 4
3 / (6x + 1) / 2 = 8 / (x + 4) / 3
[multiply both denominators to mike one denominator]
3 / 8(6x+1) = 8 / 3(x+4)
[expand brackets]
3 / (48x + 8) = 8 / (3x + 12)
[multiply by (48x + 8)]
3 = 8(48x + 8) / (3x+12)
[multiply by (3x+12)]
3(3x +12) = 4(48x + 8)
[simplify]
9x + 36 = 192x + 32
173x = 4
x = 4 / 173